A simple and economical site-directed mutagenesis method for large plasmids by direct transformation of two overlapping PCR fragments - Zhibo Yang; Zan Chen; Yueping Zhang (BioTechniques)
Despite the development of various methods and commercial kits, site-directed mutagenesis of large plasmids remains a challenge in many laboratories. A site-directed mutagenesis method was developed for large plasmids by directly transforming two overlapping PCR fragments into Escherichia coli. This method successfully generated mutations for plasmids of 8.3 kb and 11.0 kb with high efficiencies. The method only requires Q5 DNA polymerase and DpnI, which greatly reduces costs. The procedure is simple, including PCR reaction, DpnI treatment and transformation. This simple, efficient and economical site-directed mutagenesis method for large plasmids is likely to be widely applied in the future.